Comparison of success rate of arterio-venous fistula in patients with diabetes vs non-diabetes - Karki, K; Banepali, N; Hirachand, S; Mukhiya, R; Shrestha, RKN (Journal of Society of Surgeons of Nepal, 2016)
Introduction and objective: Definition of chronic renal disease is based on the presence of kidney damage or glomerular filtration rate (GFR 60 ml/min per 1.73 m2) for 3 months, irrespective of cause[1]. Once they are diagnosed as CKD, they are kept either on hemodialysis or peritoneal dialysis or patient undergo renal transplant.[2,3] With this research we may prove that even in a similar circumstances failure rate of AVF is more in diabetes patient.Materials and Methods: Total 50 patients of either gender were taken in this study. Inclusion criteria: CRF with GFR 1.5mm and venous diameter >2mm. Preoperative radial artery blood flow >30cm/min. Exclusion criteria: arterial diameter